Physiological response mechanism of European birch (Betula pendula Roth) to PEG-induced drought stress and hydration - Kou, Jing; Yan, Donghan; Qin, Baiting; Zhou, Qiang; Liu, Chunping; Zhang, Lijie (Frontiers in Plant Science, 2023)
Drought stress is also one of the important abiotic factors limiting plant growth and development, and the global temperature is rising year by year, resulting in a dry environment in most terrestrial forests, which will continue to affect the growth, development and reproduction of tree species in forests. European birch(Betula pendula Roth.) native to Europe, introduced to the mountains of eastern Liaoning in 1981 (annual precipitation of about 800mm), European birch relative to downy birch (B. pubescens)has strong adaptability and drought tolerance and cold tolerance, can grow normally in eastern Liaoning, but it is easy to be affected by drought at the seedling stage and cause death, many arid and semi-arid areas have no introduction and practical application of European birch, and there is less research on the drought resistance of European birch. This study used different concentrations of PEG-6000 treatment to simulate drought stress and clarify the changes of various growth physiological parameters and photosynthetic characteristics of European birch seedlings under drought stress, in order to investigate the physiological response mechanism of European birch under drought stress . This study used different concentrations of PEG-6000 treatment to simulate drought stress and clarify the changes of various growth physiological parameters and photosynthetic characteristics of European birch seedlings under drought stress, in order to investigate the physiological response mechanism of European birch under drought stress. The findings demonstrated that stress duration and increasing PEG concentration had a highly significant impact on the growth traits of European birch seedlings (p<0.01); With increasing stress concentration and stress time, antioxidant enzyme activity, membrane lipid peroxidation, and osmoregulatory substance concentrations increased significantly (p<0.01); With increasing stress concentration and duration, photosynthetic parameters and pigments decreased highly significantly (p<0.01); Under different PEG concentration treatments, the anatomical structure of seedling leaves changed more noticeably; there was a significant effect (p <0.05) on the change in mean stomatal length and a highly significant effect (p<0.01) on the change in mean stomatal structure. The study's findings serve as a foundation for the selection and breeding of new drought-tolerant European birch species, as well as a theoretical underpinning for the use of this species in landscaping and the promotion of new drought-tolerant species in China.